Formation Control of Multi Unmanned Aerial Vehicle Systems Based on DDS Middleware - Sami El-Ferik; Basem Almadani; Siddig Mustafa Elkhider (IEEE Access, 2020)
In this paper formation control of Unmanned Aerial Vehicle System (UAVs) is introduced. L1 controller with potential field technique and Data Distribution Service (DDS) middleware used for the navigation of the agents, which is multi-UAVs. L1 adaptive controller used to stabilizing the general equations of motion of each UAVs and the potential field technique used to formalize the followers around the leader. The exchanging data between the leader and the followers done through publisher/subscriber DDS middleware. This L1 controller has a high performance coming from a robust adaptation of it. Robustness of the L1 controller verified using Matlab Simulation. The Lyapunov method provided the analysis and stability of the framework of UAVs.